A Problem-Solving Environment to Teach Students Assembly Line Balancing Techniques - Yılmaz, Hamid; Demir, Yunus (My University, 2019)
Assembly line balancing is a production planning strategy that has been widely used in industrial applications. Most line balancing problems are known as nondeterministic polynomial time (NP-hard) problem, and they have different structures and solution methodology approaches. In this study, newly developed production planning software which is called Visual Assembly Line Balancing Software (VALBS) is introduced for educational purposes. The aim of the software is to support teaching activity for assembly line balancing techniques; facilitate understanding characteristics of different assembly lines and solution approaches, and enable to compare the results of them. The proposed VALBS is easy to use in various manufacturing environments, and suitable to support teaching line balancing procedures in undergraduate students. The software was used in classes of industrial and mechanical engineering students and feedbacks of students measured by Likert Scale survey. The results show that proposed visual software is an effective method to teach line balancing procedures.

Montaj hattı dengeleme, endüstriyel uygulamalarda yaygın olarak kullanılan bir üretim planlama stratejisidir. Çoğu montaj hattı dengeleme problemi, deterministtik olmayan polinom zamanlı (NP-zor) problem olarak bilinir ve farklı yapılara ve çözüm metodolojisi yaklaşımlarına sahiptir. Bu çalışmada, Görsel Montaj Hattı Dengeleme Yazılımı (GMHDY) adı verilen yeni geliştirilen üretim planlama yazılımı, eğitim amaçlı olarak tanıtılmıştır. Yazılımın amacı, montaj hattı dengeleme teknikleri için öğretim faaliyetlerini desteklemek, farklı montaj hatlarının ve çözüm yaklaşımlarının özelliklerini anlamak ve sonuçlarının karşılaştırılmasını sağlamaktır. Önerilen GMHDY, çeşitli üretim ortamları için kullanımı kolay ve lisans öğrencileri için montaj hattı dengeleme yöntemlerinin öğretimini desteklemektedir. Yazılım, endüstri ve makine mühendisliği öğrencilerine kullandırılmış ve öğrenci geri bildirimleri, Likert ölçekli anket ile değerlendirilmiştir. Sonuçlar, önerilen görsel yazılımın hat dengeleme yöntemlerini öğretmek için etkili bir araç olduğunu göstermektedir.
Öğrencilere Montaj Hattı Dengeleme Tekniklerini Öğretmek için Bir Problem Çözme Ortamı
Keywords: [No Keywords]